Mitochondrial Damage and Mitochondria-Targeted Antioxidant Protection in LPS-Induced Acute Kidney Injury - Egor Y. Plotnikov; Irina B. Pevzner; Ljubava D. Zorova; Valery P. Chernikov; Andrey N. Prusov; Igor I. Kireev; Denis N. Silachev; Vladimir P. Skulachev; Dmitry B. Zorov (Antioxidants, 2019)
Induced and frequently unwanted alterations in the mitochondrial structure and functions are a key component of the pathological cascade in many kidney pathologies, including those associated with acute damage. One of the principal pathogenic elements causing mitochondrial dysfunction in Acute Kidney Injury (AKI) is oxidative stress. After ischemia and nephrotoxic action of drugs, sepsis and systemic inflammation are the most frequent causes of AKI. As the kidney suffers from oxidative stress during sepsis, one of the most promising approaches to alleviate such damaging consequences is the use of antioxidants. Considering administration of lipopolysaccharide (LPS) as a model of sepsis, we demonstrate that the mitochondria of neonatal renal tissue are severely affected by LPS-induced AKI, with pathological ultrastructural changes observed in both the mitochondria of the renal tubular epithelium and the vascular endothelium. Upon mitochondrial damage, we evaluated the effect of the mitochondria-targeted antioxidant plastoquinol decylrhodamine 19 (SkQR1) on the development of acute renal failure in newborn rats associated with systemic inflammation induced by the administration of LPS. We found that SkQR1 administration 3 h before LPS led to decreased urinal expression of the AKI marker neutrophil gelatinase-associated lipocalin 2 (NGAL), in addition to a decrease in urea and creatinine levels in the blood. Additionally, an observed impairment of proliferative activity in the neonatal kidney caused by LPS treatment was also prevented by the treatment of rat pups with SkQR1. Thus, one of the key events for renal tissue damage in neonatal sepsis is an alteration in the structure and function of the mitochondria and the mitochondria-targeted antioxidant SkQR1 is an effective nephroprotective agent, which protects the neonatal kidney from sepsis-induced AKI.